ANALISIS STRATEGI GURU DALAM MENGIMPLEMENTASIKAN MODUL AJAR KURIKULUM MERDEKA DI SD NEGERI 2 JAYA - Faradilla Sandy; Mislinawati; Suci Fitriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The implementation of the Independent Curriculum has just been implemented at SD Negeri 2 Jaya, especially in grades IV, V, and VI. In implementing the Independent Curriculum Teaching Module, especially in science learning, there are still several obstacles, such as teachers' lack of understanding of the Teaching Module structure, limited infrastructure, and differences in student abilities. This study aims to analyze teacher strategies in implementing the Independent Curriculum Teaching Module at SD Negeri 2 Jaya. This study uses a qualitative approach with a descriptive type. The research subjects consisted of three teachers in grades IV, V, and VI. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used an interactive model that includes data reduction, data presentation, and drawing conclusions. Based on the results of the study, it shows that teachers have implemented the Teaching Module very well, especially in the components of learning objectives, learning activities, and assessment. Teachers also use various strategies such as simple media, group discussions, and the use of technology in learning. The conclusion of this study is that the teachers' strategies in implementing the Independent Curriculum Teaching Module at SD Negeri 2 Jaya are considered good, but still need improvement, especially in the comprehensive and optimal development of the teaching module components. Therefore, ongoing training and mentoring are needed for teachers to ensure more effective implementation of the Independent Curriculum.